Tectonics of the Petrovo-Hnutivian ore knot of the Near-Azovian area - Shatalov, N.N. (Reports of the National Academy of Sciences of Ukraine, 2014)
The results of investigations for the large structural Petrovo-Hnutivian ore knot within the Near-Azovian megablock of the Ukrainian Shield are presented. The features of the fault-block tectonics and its influence on forming the ore knot are defined. The Kalmius, Oktiabrsk, and other fault zones of the orthogonal and diagonal systems and their significance for the localization of metasomatites and the exceptional ore-bearing fluorite-parisite rare-earth dyke are characterized. The mineral composition of the dyke is analyzed.